2017
DOI: 10.1371/journal.pone.0185451
|View full text |Cite
|
Sign up to set email alerts
|

Relations between mental health team characteristics and work role performance

Abstract: Effective mental health care requires a high performing, interprofessional team. Among 79 mental health teams in Quebec (Canada), this exploratory study aims to 1) determine the association between work role performance and a wide range of variables related to team effectiveness according to the literature, and to 2) using structural equation modelling, assess the covariance between each of these variables as well as the correlation with other exogenous variables. Work role performance was measured with an ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
5
0
3
Order By: Relevance
“…19 Working in a multidisciplinary team implies one more step toward the understanding and the collective treatment of the mental disease. Fleury et al, 48 as is shown as well in this study, mention the importance of coordination and networking. The findings of Kress et al 49 are in line with this study in terms of the lack of time and personnel to provide good care.…”
Section: Discussionsupporting
confidence: 79%
“…19 Working in a multidisciplinary team implies one more step toward the understanding and the collective treatment of the mental disease. Fleury et al, 48 as is shown as well in this study, mention the importance of coordination and networking. The findings of Kress et al 49 are in line with this study in terms of the lack of time and personnel to provide good care.…”
Section: Discussionsupporting
confidence: 79%
“…Kallio, K., Kallio, T. [25] Work efficiency draws attention to the team's behaviour and actions that could increase work productivity. Fleury et al [26] Shifting actions, behaviours and results that the employee achieves while working for the good of the organization. Sujatha, Krishnaveni [27] Three main points emerge in the dimension of emotional intelligence: the ability to recognize one's own and others' emotions and to adequately interpret them; the stress-management skill, which emerges from understanding; the ability to adequately show emotions through communication.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Basé sur les résultats d'un programme de recherche comportant plusieurs publications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] , cet article résume les principaux changements apportés dans les services et les retombées sur les équipes de soins et les usagers suite à la réforme en SM. Plus spécifiquement, il vise à évaluer : 1.a) dans 11 réseaux locaux de services, le niveau d'implantation des principaux objectifs poursuivis par le PASM (recensés plus haut) et les facteurs ayant influencé son implantation ainsi que 1.b) d'estimer la performance des équipes de SM selon leur coordonnateur ; 2) les processus pouvant influencer la qualité des services selon les professionnels des équipes de SM, à partir d'un sous-échantillon de quatre réseaux ; et 3) les effets des structures et des processus d'équipe sur les usagers -aussi à partir de ces quatre réseaux.…”
Section: Résumé De L'articleunclassified
“…La recherche a aussi porté sur les déterminants de la performance (définie comme les dynamiques individuelles et d'équipe contribuant à l'efficacité, et reliée à la maîtrise des tâches et la capacité d'adaptation ou d'innovation) 32 de 79 équipes de SM selon le point de vue de leur coordonnateur (figure 1). Ces travaux 17,21…”
Section: Performance Des éQuipes De Sm Selon Leurs Coordonnateursunclassified